IMPROVING THE STUDENTS’ READING COMPREHENSION ON NARRATIVES THROUGH CIREBONESE LOCAL CONTENT BASED TEXT MATERIAL - Krista Renggana; Susilawati Susilawati (Concept : Community Concern for English Pedagogy and Teaching, 2017)
This study aimed at (1) to figure out the process of the students’ learning in reading comprehension on narratives through Cirebonese local content as based text material at the second grade students of SMPN 1 Jatibarang and (2) to find out the result of the student’s achievement in reading comprehension by using Cirebonese local content based text material in improving their comprehension on narratives at the second grade students of SMPN 1 Jatibarang. The research focused in the second grade I students of SMP N 1 Jatibarang Kabupaten Indramayu in academic year 2017/2018 which consist of 37 students.The study was classroom action research (CAR). The steps of the study are planing the action, implementing the action, observation, and refleting the action. The use of Cirebonese Local Content in reading comprehension can also improve the learning outcome. It can be seen from the results of the study showing an increase in students’ reading comprehension, which is shown by the students’ mean score of reading test results from Cycle I to pre-action activity increased from 64.9 into 76.5. The number of students who achieved a completeness study in the pre-action stage are 14 students. In Cycle I students' mean score increased to 76.5 with 22 students who passed the completeness score. Key words: Reading Comprehension, Narrative, Cirebonese Local Content